John of Salisbury’s Skepticism. A Veritable Exhortation to Prudence (hortamen ad prudentiam) - Bogdan Guguianu (Anastasis: Research in Medieval Culture and Art, 2022)
The purpose of this article is to bring up some of John of Salisbury’s skeptical theses (1115/20 – 1180) and their impact on the rest of his works. The introduction will deal with the context of the so-called ”medieval skepticism”, the first part will tackle John of Salisbury’s approaches to skepticism, the second part will attempt to connect some concepts in his work to a few ancient skeptics, while the last part will try to concretely identify elements of skepticism in John of Salisbury’s theological discourse. Suffice it to say that, in the end, we will draw some conclusions related to the subject. The article’s goal is to take notice, without the pretension of being exhaustive, of the polymorphous way in which the epistemologically skeptical attitude of John of Salisbury influenced different aspects of his doctrine.